An AIEgen/graphene oxide nanocomposite (AIEgen@GO)‐based two‐stage "turn‐on" nucleic acid biosensor for rapid detection of SARS‐CoV‐2 viral sequence. Issue 1 (11th April 2022) - Zhang, Qin; Yin, Bohan; Hao, Jianhua; Ma, Linjie; Huang, Yingying; Shao, Xueying; Li, Chuanqi; Chu, Zhiqin; Yi, Changqing; Wong, Siu Hong Dexter; Yang, Mo
Abstract: The ongoing outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) pandemic has posed significant challenges in early viral diagnosis. Hence, it is urgently desirable to develop a rapid, inexpensive, and sensitive method to aid point‐of‐care SARS‐CoV‐2 detection. In this work, we report a highly sequence‐specific biosensor based on nanocomposites with aggregation‐induced emission luminogens (AIEgen)‐labeled oligonucleotide probes on graphene oxide nanosheets (AIEgen@GO) for one step‐detection of SARS‐CoV‐2‐specific nucleic acid sequences ( Orf1ab or N genes). A dual "turn‐on" mechanism based on AIEgen@GO was established for viral nucleic acids detection. Here, the first‐stage fluorescence recovery was due to dissociation of the AIEgen from GO surface in the presence of target viral nucleic acid, and the second‐stage enhancement of AIE‐based fluorescent signal was due to the formation of a nucleic acid duplex to restrict the intramolecular rotation of the AIEgen. Furthermore, the feasibility of our platform for diagnostic application was demonstrated by detecting SARS‐CoV‐2 virus plasmids containing both Orf1ab and N genes with rapid detection around 1 h and good sensitivity at pM level without amplification. Our platform shows great promise in assisting the initial rapid detection of the SARS‐CoV‐2 nucleic acid sequence before utilizing quantitative reverse transcription‐polymerase chain reaction for second confirmation. Abstract : An AIEgen‐graphene oxide (GO) nanocomposite‐based assay is designed for rapid detection of SARS‐CoV‐2 nucleic acids. The sensing mechanism is based on two‐stage fluorescence signal recovery due to fluorescence resonance energy transfer (FRET) effect by detaching AIEgen from GO surface and restricted intramolecular rotation (RIR) effect by formation of nucleic acid duplexes.